Rasch Validation of the Arabic Version of the Chedoke–McMaster Attitudes Toward Children With Handicaps (CATCH-AR) Scale - Alnahdi, Ghaleb H. (Frontiers in Psychology, 2020)
Students’ attitudes towards peers with disabilities are crucial for the social inclusion of the latter. Therefore, understanding such attitudes can help improve the social inclusion of students with disabilities. This study aimed to examine the psychometric properties of the Arabic version of the Chedoke–McMaster Attitudes towards Children with Handicaps scale. Data were collected from 415 elementary school students, including 232 (56%) girls and 183 (44%) boys, in grades three to six in Saudi Arabia. The psychometric properties of the scale were examined using the Rasch analysis procedures. The results did not support the unidimensionality of the 36-item scale. Dividing items based on whether they are negatively or positively phrased improved the scale fit. Both the 15-item (positive phrasing) and the 18-item (negative phrasing) scales were supported by the Rasch analysis as unidimensional scales.